(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
This paper deals with the oscillation of third order impulsive differential equations with delay. The results of this paper improve and extend some results for the differential equations without impulses. Some examples are givento illustrate the main results.